Thermal cracking of a railway wheel tread due to tread braking–critical crack sizes and in fluence of repeated thermal cycles. (January 2013) - Caprioli, Sara; Vernersson, Tore; Ekberg, Anders
A numerical study of tread cracking due to thermal loading induced by tread braking is carried out. The analysis features a computationally efficient approach combining two-dimensional finite-element simulations with an analytical evaluation of resulting stress intensity factors. The analysis identifies critical sizes for when existing surface cracks are prone to propagate under thermal loading and resulting crack lengths after propagation. The results imply that fully functional brake systems are not likely to induce thermal crack propagation under normal stop braking, but that with pre-existing defects, a severe drag braking due to malfunctioning brakes may cause very deep cracking. Furthermore, the analysis concludes the cracking to be a static phenomenon related to the most severe brake cycle, i.e. later brake cycles of similar or lower severity will not cause any significant propagation of existing cracks. Additional three-dimensional finite-element simulations are used to validate the model, and they indicate two-dimensional results to be on the conservative side. This paper originated from the 2011 IHHA Conference.